2007
DOI: 10.1063/1.2764448
|View full text |Cite
|
Sign up to set email alerts
|

Polarization-induced valence-band alignments at cation- and anion-polar InN∕GaN heterojunctions

Abstract: AlN and GaN epitaxial heterojunctions on 6H-SiC(0001): Valence band offsets and polarization fields

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 19 publications
(13 reference statements)
1
26
1
Order By: Relevance
“…These experimental results are in contrast to measurements of polarization effects at interfaces between two polar crystalline materials such as InN and GaN. 50 In this case as in other polar-polar crystalline interfaces, the interface dipole due to the polarization charge is manifested as an evident change in the VBO for opposite polar configurations. However, the relatively small band bending on Ga-and N-face GaN indicated that the polarization charge is largely screened by a high concentration of interface states.…”
Section: Interface Dipole and Polarizationcontrasting
confidence: 53%
“…These experimental results are in contrast to measurements of polarization effects at interfaces between two polar crystalline materials such as InN and GaN. 50 In this case as in other polar-polar crystalline interfaces, the interface dipole due to the polarization charge is manifested as an evident change in the VBO for opposite polar configurations. However, the relatively small band bending on Ga-and N-face GaN indicated that the polarization charge is largely screened by a high concentration of interface states.…”
Section: Interface Dipole and Polarizationcontrasting
confidence: 53%
“…The VB offset between GaN and InN has been measured in a number of studies. 4,[21][22][23][24][25][26][27][28] The most recent experimental study reported an offset of 0.58 ± 0.08 eV. 28 However, accurately measuring the offset is very difficult as seen from the wide spread (between 0.6 and 1.1 eV) of the reported experimental values.…”
Section: Alloys Ofmentioning
confidence: 99%
“…28 However, accurately measuring the offset is very difficult as seen from the wide spread (between 0.6 and 1.1 eV) of the reported experimental values. [21][22][23][24][25][26][27][28] 32 Band offsets for AlN, GaN, and AlGaN alloys are also important for device applications such as lasers and HEMTs. The variation in reported experimental VB offsets is, again, quite large [0.…”
Section: Alloys Ofmentioning
confidence: 99%
“…Chung-Lin Wu, 1,a͒ Hong-Mao Lee, 1 Cheng-Tai Kuo, 1 Chia-Hao Chen, 2 A method for studying heterojunction band lineups on the submicrometer scale is demonstrated by using synchrotron-radiation photoelectron microscopy and spectroscopy. In particular, an in situ sample cleavage technique is adopted here to reveal the cross-sectional, nonpolar a-plane face of InN / GaN heterojunction grown on Si͑111͒ along the polar −c axis with fully relaxed lattice structure, eliminating the polarization effects associated with the interface charge/dipole normal to the cleaved surface.…”
Section: Cross-sectional Scanning Photoelectron Microscopy and Spectrmentioning
confidence: 99%